Electrical Charge State Manipulation of Single Silicon Vacancies in a Silicon Carbide Quantum Optoelectronic Device - Widmann, Matthias; Niethammer, Matthias; Fedyanin, Dmitry Yu; Khramtsov, Igor A.; Rendler, Torsten; Booker, Ian D.; Ul Hassan, Jawad; Morioka, Naoya; Chen, Yu Chen; Ivanov, Ivan G.; Son, Nguyen Tien; Ohshima, Takeshi; et al. (Nano Letters, 2019)
Color centers with long-lived spins are established platforms for quantum sensing and quantum information applications. Color centers exist in different charge states, each of them with distinct optical and spin properties. Application to quantum technology requires the capability to access and stabilize charge states for each specific task. Here, we investigate charge state manipulation of individual silicon vacancies in silicon carbide, a system which has recently shown a unique combination of long spin coherence time and ultrastable spin-selective optical transitions. In particular, we demonstrate charge state switching through the bias applied to the color center in an integrated silicon carbide optoelectronic device. We show that the electronic environment defined by the doping profile and the distribution of other defects in the device plays a key role for charge state control. Our experimental results and numerical modeling evidence that control of these complex interactions can, under certain conditions, enhance the photon emission rate. These findings open the way for deterministic control over the charge state of spin-active color centers for quantum technology and provide novel techniques for monitoring doping profiles and voltage sensing in microscopic devices.
CRIS-Team Scopus Importer:2019-10-18
Keywords: materials science; multidisciplinary; nanotechnology; semiconductors